The 2013 ACC/AHA 10-year atherosclerotic cardiovascular disease risk index is better than SCORE and QRisk II in rheumatoid arthritis: is it enough? - SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT; DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2015)
Objective. To determine the ability of the new American College of Cardiology and American Heart Association (ACC/AHA) 10-year atherosclerotic cardiovascular disease (ASCVD) risk algorithm in detecting high cardiovascular (CV) risk, RA patients identified by carotid ultrasonography (US) were compared with Systematic Coronary Risk Evaluation (SCORE) and QRisk II algorithms. Methods. SCORE, QRisk II, 2013 ACC/AHA 10-year ASCVD risk and EULAR recommended modified versions were calculated in 216 RA patients. In sonographic evaluation, carotid intima-media thickness >0.90 mm and/or carotid plaques were used as the gold standard test for subclinical atherosclerosis and high CV risk (US+). Results. Eleven (5.1%), 15 (6.9%) and 44 (20.4%) patients were defined as having high CV risk according to SCORE, QRisk II and ACC/AHA 10-year ASCVD risk, respectively. Fifty-two (24.1%) patients were US+ and of those, 8 (15.4%), 7 (13.5%) and 23 (44.2%) patients were classified as high CV risk according to SCORE, QRisk II and ACC/AHA 10-year ASCVD risk, respectively. The ACC/AHA 10-year ASCVD risk index better identified US+ patients than SCORE and QRisk II (P < 0.0001). With EULAR modification, reclassification from moderate to high risk occurred only in two, five and seven patients according to SCORE, QRisk II and ACC/AHA 10-year ASCVD risk, respectively. Conclusion. The 2013 ACC/AHA 10-year ASCVD risk estimator was better than the SCORE and QRisk II indices in RA, but still failed to identify 55% of high risk patients. Furthermore adjustment of threshold and EULAR modification did not work well.
Keywords: cardiovascular risk estimation; SCORE; QRisk II; ACC/AHA 10-year ASCVD; carotid intima-media thickness; INTIMA-MEDIA THICKNESS; NECROSIS-FACTOR INHIBITORS; MYOCARDIAL-INFARCTION; CAROTID ULTRASOUND; AMERICAN-COLLEGE; MORTALITY; METAANALYSIS; STRATIFICATION; CLASSIFICATION; POPULATION